Before solving the problem, please note the problem has been changed as "(3x+y+z)p + (x+y+z)q = 2(z+y)" instead of "(3x+y-z)p + (x+y+z)q = 2(z+y)".
Consider, "(3x+y+z)p + (x+y+z)q = 2(z+y)".
The auxiliary equation is,
"\\dfrac{dx}{3x+y+z}=\\dfrac{dy}{x+y+z}=\\dfrac{dz}{2(z+y)}."
Using the multipliers 1, -3, 1 each of the above ratio is equal to
"\\dfrac{dx-3dy+dz}{3x+y+z-3x-3y-3z+2z+2y}=\\dfrac{dx-3dy+dz}{0}"
Thus,
"dx-3dy+dz = 0"
Integrating we get, "x-3y+z=c_{1}."
Each of the ratio in the auxiliary equation is equal to
"\\dfrac{dx+dy+dz}{3x+y+z+x+y+z+2z+2y}=\\dfrac{dx-dy-dz}{3x+y+z-x-y-z-2z-2y}\\\\~\\\\\n\\dfrac{dx+dy+dz}{4(x+y+z)}=\\dfrac{dx-dy-dz}{2(x-y-z)}\\\\~\\\\\n\\dfrac{dx+dy+dz}{2(x+y+z)}=\\dfrac{dx-dy-dz}{(x-y-z)}\\\\~\\\\\n\\text{Integrating,} \\\\\n\\dfrac{1}{2}\\ln(x+y+z)=\\ln(x-y-z)+\\ln c_{2}\\\\~\\\\\n\\ln\\bigg(\\dfrac{\\sqrt{x+y+z}}{x-y-z}\\bigg)=\\ln c_{2}\\\\~\\\\\n\\dfrac{\\sqrt{x+y+z}}{x-y-z} = c_{2}."
Hence the general solution is, "\\phi(c_{1},c_{2})=0"
"\\phi\\bigg(x-3y+z, \\dfrac{\\sqrt{x+y+z}}{x-y-z}\\bigg)=0"
Comments
Leave a comment